DISPELLING “LANGUAGE MYTHS” IN ENGLISH-MEDIUM INSTRUCTION: DESFAZENDO “MITOS DA LINGUAGEM” EM ENGLISH-MEDIUM INSTRUCTION - Pusey, Kerry (Revista CBTecLE, 2022)
This paper attempts to dispel some commonly held, but potentially faulty ideas about the nature of English language use in English-medium instruction (EMI) contexts - what I refer to as EMI “myths.” Drawing on a synthesis of transdisciplinary scholarship from the field of applied linguistics, I discuss three dimensions of English language use in EMI contexts that tend to be misunderstood, namely: (1) the multilingual nature of EMI; (2) the relativity of English language proficiency; and (3) the role of multimodality in EMI classroom interaction. In dispelling the myths that surround these dimensions of language use, this paper seeks to legitimize translingual practices in EMI. Ultimately, the paper aims to inspire new ways of thinking about how language(s) are conceived of in EMI contexts, which may serve as a point of departure for further research and practical work.